Pendampingan Pembentukan Tim Pemasaran Digital UMKM Desa Cibogo - Sony Hartono; Riani Budiarsih; Roby Syaiful Ubed (Asosiasi Dosen Akuntansi Indonesia, 2022)
Until 2022, most of the SMEs in Cibogo Village have not used digital marketing in marketing their products. This condition causes Cibogo MSME products to only rely on market share around Cibogo Village. This is ironic considering that Cibogo Village is located near large urban-scale housing estates, namely BSD, Gading Serpong, Alam Sutera and Bintaro Jaya which have a large market share. However, the desire of MSMEs in Cibogo Village to utilize digital marketing to expand the market is constrained by time and the mastery of information technology by MSME actors, so that until now conventional marketing methods are their priority. To facilitate these obstacles, a Cibogo MSME digital marketing team was formed consisting of Cibogo Village youths. The formation of this digital marketing team begins with the recruitment stage to the training and mentoring stage which lasts for 4 months. Until August 2022, the training stage and the establishment of the Cibogo Village MSME storefront are still ongoing in one of the online marketplaces and several social media. The existence of the Digital Marketing Team is very helpful for MSMEs in Cibogo Village who do not have time to market their products online, so that MSME actors can focus on being creative and innovating in producing products. In the end, MSME players do not mess around with online marketing, but still have the opportunity to get a wider market share through the digital marketing team.